Essential role of ryanodine receptor 2 phosphorylation in the effect of azumolene on ventricular arrhythmia vulnerability in a rabbit heart model. (31st October 2018) - Si, Daoyuan; Azam, Mohammed Ali; Lai, Patrick F. H.; Zamiri, Nima; Kichigina, Galina; Asta, John; Massé, Stéphane; Bokhari, Mahmoud M.; Porta‐Sánchez, Andreu; Labos, Christopher; Sun, Huan; Yang, Ping; et al.
Abstract: Introduction: Following long‐duration ventricular fibrillation (LDVF), reinitiation of ventricular fibrillation (VF) poses a major challenge during resuscitation. Ryanodine receptor 2 (RyR2) becomes dysfunctional following VF. The relationship between LDVF, RyR2 modulation, and ventricular refibrillation, as well as the role of RyR2 phosphorylation, remains unknown. Methods: Langendorff‐perfused rabbit hearts were subjected to global ischemia and treated with azumolene (or vehicle alone in controls) upon reperfusion. After electrical induction of an initial LDVF episode, each heart was further stimulated electrically to assess reinducibility of VF. Myocardial calcium dynamics were assessed by optical mapping. RyR2 phosphorylation in left ventricular tissue extracts was analyzed by Western blot analysis. Results: Fewer episodes of refibrillation (lasting ≥ 10 seconds) were induced in azumolene‐treated hearts than in controls ( P  = 0.01); however, this reduction in refibrillation was abrogated in the presence of the protein kinase A inhibitor H89. Spontaneous calcium elevation was significantly lower in azumolene‐treated hearts than in control hearts ( P  = 0.002) and in hearts pretreated with H89 before azumolene ( P  = 0.01). RyR2 phosphorylation at Ser2808 was higher in hearts subjected to LDVF than in non‐VF hearts ( P  = 0.029), while no significant difference was found at Ser2814. Pretreatment with H89 led to significantly less RyR2 phosphorylation at Ser2808 ( P  = 0.04) after LDVF, while pretreatment with KN93 or azumolene alone showed no effects on RyR2 phosphorylation. Conclusion: Ventricular refibrillation following LDVF was reduced by azumolene, which also improves calcium dynamics. RyR2 phosphorylation at Ser2808 is a prerequisite for the beneficial effects of azumolene.